Inhibition of Key Virulence Enzymes of Botrytis Cinerea by Flavonoids from the Antarctic Plant Colobanthus Quitensis - Zuniga-Navarro, G; Contreras-Arredondo, R (John Wiley and Sons Inc, 2025)
This study investigates the antifungal efficacy of flavonoids derived from Colobanthus quitensis against key virulence-related enzymes implicated in the pathogenic mechanisms of Botrytis cinerea. The flavonoids swertiajaponin, schaftoside, vitexin, and saponarin significantly inhibited pectinase, cellulase, and laccase activity. Specifically, swertiajaponin showed mixed inhibition of pectinase and cellulase, characterized by high affinity (low inhibition constant -Ki−) for enzyme-substrate complexes. Schaftoside showed mixed inhibition of pectinase and competitive inhibition of laccase, effectively reducing enzymatic activity by competing directly with the substrate. In contrast, vitexin showed competitive inhibition of pectinase and non-competitive inhibition of laccase, suggesting it induces conformational changes within the enzyme. Finally, saponarin uniquely showed uncompetitive inhibition of laccase, stabilizing the enzyme-substrate complex and thereby markedly reducing catalytic turnover. Supported by kinetic parameters (maximum velocity -Vmax-, Michaelis constant -Km-, and Ki), these findings highlight the potential of flavonoids from C. quitensis as natural fungicides, offering a sustainable and eco-friendly alternative to synthetic fungicides for managing agricultural diseases. © 2024 Wiley-VHCA AG, Zurich, Switzerland.